IMPLEMENTATION OF THE DMAIC APPROACH FOR QUALITY IMPROVEMENT AT THE ELASTIC TAPE INDUSTRY - Hibarkah Kurnia; Choesnul Jaqin; Hasiholan Manurung (Departemen Teknik Industri, Fakultas Teknik, Universitas Diponegoro, 2022)
The scope of this research is in one of the textile industries with elastic tape produced on the weaving machine, which has decreased production due to production defects that do not meet the target. This research aims to determine the leading causes of dominant defects, increase the sigma level with Six Sigma methods, and propose improvements to be included in the Key Performance Indicators (KPI) method. The results of this study that the dominant factor causing the defect is the curved elastic tape defect, which consists of the machine factor, and the method. Factors driving the machine include the hook like a side thread lock that is often bent and the difference in the thickness of the tape between the left, middle and right. The causative factor of this method is checking the thickness of the elastic band only in the center position. The results of corrective actions impact increasing the sigma level by 10% from 3.3339 to 3.6832. In contrast, repair defects can reduce defects before repair by 18.92% and after repair by 9.23%. It is proposed to be included in the KPI so that the weaving department can control and be enthusiastic about continuous improvement.